Development of RLK-Unet: a clinically favorable deep learning algorithm for brain metastasis detection and treatment response assessment - Son, Seungyeon; Joo, Bio; Park, Mina; Suh, Sang Hyun; Oh, Hee Sang; Kim, Jun Won; Lee, Seoyoung; Ahn, Sung Jun; Lee, Jong-Min (Frontiers in Oncology, 2024)
Purpose/objective(s): Previous deep learning (DL) algorithms for brain metastasis (BM) detection and segmentation have not been commonly used in clinics because they produce false-positive findings, require multiple sequences, and do not reflect physiological properties such as necrosis. The aim of this study was to develop a more clinically favorable DL algorithm (RLK-Unet) using a single sequence reflecting necrosis and apply it to automated treatment response assessment.Methods and materials: A total of 128 patients with 1339 BMs, who underwent BM magnetic resonance imaging using the contrast-enhanced 3D T1 weighted (T1WI) turbo spin-echo black blood sequence, were included in the development of the DL algorithm. Fifty-eight patients with 629 BMs were assessed for treatment response. The detection sensitivity, precision, Dice similarity coefficient (DSC), and agreement of treatment response assessments between neuroradiologists and RLK-Unet were assessed.Results: RLK-Unet demonstrated a sensitivity of 86.9% and a precision of 79.6% for BMs and had a DSC of 0.663. Segmentation performance was better in the subgroup with larger BMs (DSC, 0.843). The agreement in the response assessment for BMs between the radiologists and RLK-Unet was excellent (intraclass correlation, 0.84).Conclusions: RLK-Unet yielded accurate detection and segmentation of BM and could assist clinicians in treatment response assessment.